Implementing a Hybrid Summer Transition Program - Gibson, Stephen M.; Brinkley, Kendra; Griggs, Lauren A.; James, Briana N.; Smith, Mychal; Schwitzerlett, Mark; Waller, LaChelle M.; Hargraves, Rosalyn Hobson (Frontiers in Education, 2021)
The mission of the Virginia Commonwealth University Louis Stokes Alliance for Minority Participation (VCU LSAMP) is to increase the retention and graduation rates of students from underrepresented racial and ethnic groups in science, technology, engineering, and mathematics (STEM) majors and those who matriculate into graduate programs. VCU LSAMP offers a hybrid summer transition program (HSTP) focused on facilitating the high school to college and two-year to four-year college transition process for students majoring in STEM disciplines. The goals of the program are to (1) build community among a cohort of students, (2) orient students to VCU, (3) prepare students for the academic rigors of their first year in a STEM discipline at VCU, (4) expose students to opportunities and careers in STEM, (5) engage them in the VCU LSAMP program, and (6) provide financial support. Five distinct components of the VCU HSTP are (1) a six-week online summer component, (2) a one week on-campus orientation, (3) a Design Project Challenge, (4) a transfer student track, and (5) an academic year component. Evaluation data reveals that the HSTP assisted participants with adjustment to the college schedule and setting, facilitated the formation of study groups, and increased overall motivation to graduate. The online courses helped familiarize students with both the academic topics in their chemistry and mathematics classes and the behaviors and norms of STEM majors. On average, participants in the HSTP had higher retention (85%) and graduation (73%) rates when compared with their peers (81% and 64% respectively). Furthermore, those students who complete the online classes’ requirements had a higher probability of receiving a grade of B or better in their first mathematics or science class.